An Architectural Model for Structure of Summary Electronic Health Record - Hamid Moghaddasi; Maryam Jahanbakhsh; Reza Rabiei; Farkhondeh Asadi (مدیریت اطلاعات سلامت, 2016)
Introduction: Achieving the potential benefits of electronic health record (EHR) requires data interoperability. Interoperability of a summary record is more practical than a detailed record. Interoperability requirements include identification and development uniform and standard EHR structure. This study aimed to provide an architecture model for the summary record.